Synthesis and optoelectronic properties of dinuclear iridium (III) complexes containing deep blue fluorescence chromophore in the single-emissive-layer WPLEDs. Issue 52 (29th December 2016) - Hao, Zhaoran; Jiang, Haigang; Liu, Yu; Zhang, Youming; Yu, Junting; Wang, Yafei; Tan, Hua; Su, Shijian; Zhu, Weiguo
Abstract: To explore the influence of molecular structure on formation excimer and obtain high efficiency white polymer light-emitting devices (WPLEDs), two novel blue-emitting dinuclear cyclometalated iridium (III) complexes, namely C8 DBCzC6 -DF2 Ir(pic) and DPy(TPA)-C6 DBCzC6 -DF2 Ir(pic), have been successfully synthesized and characterized, in which DBCz is 3, 6-diphenyl-carbazole bridged core, DPy(TPA) is 4, 4′-di(pyren-1-yl)triphenylamine deep blue-emitting fluorescent chromophore, DF2 Ir(pic) is dinuclear iridium (III) bis[(4, 6-difluorophenyl)-pyridinato-N, C 2′ ](picolinate) blue-emitting phosphorescent chromophore, and C6 is an nonconjugated dioxyhexyloxy linkage, respectively, and each parts of molecular skeleton are wired through nonconjugated ether linkage. Their thermal, electrochemical and optophysical properties were primarily investigated. Near white light emission were obtained in the C8 DBCzC6 -DF2 Ir(pic)-doped devices using a blend of polyvinylcarbazole (PVK) and 2-(4-biphenyl)-5-(4- tert -butylphenyl)-1, 3, 4-oxadiazole (PBD) as a host matrix at dopant concentrations of 1 wt%. However, after triphenylamine functionalized pyrene DPy(TPA) replaced the alkyl chain C6 unit, at first unexpected, substitution effect occurs, more stable white light emissions with the CIE coordinates of (0.297 ± 0.009, 0.345 ± 0.007) and a maximum brightness of 961 cd/m 2 were observed in the same device at the doping concentrations of 8 wt% under different applied voltages from 8 to 13 V. The results indicate that aggregation/excimer emissions of iridium (III) complexes can be effectively tuned by inserting a deep blue fluorescent chromophore into the dual picolinic acid derivative, and it aslo be an efficient way to get white-emitting WPLEDs. Graphical abstract: A novel dinuclear iridium (III) complex of DPy(TPA)-C6 DBCzC6 -DF2 Ir(pic) containing deep blue-emitting fluorophore unit DPy(TPA) was successfully synthesized and characterized. Using this dinuclear iridium (III) complex as a single-component emitter and a blend of PVK-PBD as a host matrix, under different applied voltages from 8 to 13 V, stable white emission with the CIE coordinates (0.297 ± 0.009, 0.345 ± 0.007) and a maximum brightness of 961 cd/m 2 was achieved in the single-emissive-layer PLEDs at the doping concentrations of 8 wt%. Highlights: A blue-emitting fluorophore chromophore-functionalized dinuclear iridium complex of DPy(TPA)-C6 DBCzC6 -DF2 Ir(pic) was synthesized. The optophysical and electroluminescent properties of DPy(TPA)-C6 DBCzC6 - DF2 Ir(pic) were investigated. Stable white emission was observed in its doped single-emissive-layer PLEDs. A maximum brightness of 961 cd/m 2 was obtained in the PLEDs.